2020
DOI: 10.1111/odi.13749
|View full text |Cite
|
Sign up to set email alerts
|

The effect of topical chamomile in the prevention of chemotherapy‐induced oral mucositis: A randomized clinical trial

Abstract: Objective To clinically assess the effectiveness of topical chamomile oral gel in the prevention of chemotherapy‐induced oral mucositis. Material and methods A parallel single‐blind randomized clinical trial conducted on 45 patients who were undergoing chemotherapy. Patients were assigned to three equal groups. Group I received conventional symptomatic treatment that included antifungal agents (Miconaz oral gel, Medical Union Pharmaceuticals), topical anesthetics, and anti‐inflammatory agent (BBC oral spray, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…In general, evidence from 7 studies 35 , 36 , 38 , 42 , 45 , 47 , 50 showed that chamomile use with the mentioned concentrations and durations can reduce oral mucositis in cancer patients. Only one study 52 reported no effect of chamomile on oral mucositis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, evidence from 7 studies 35 , 36 , 38 , 42 , 45 , 47 , 50 showed that chamomile use with the mentioned concentrations and durations can reduce oral mucositis in cancer patients. Only one study 52 reported no effect of chamomile on oral mucositis.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published in English from 1991 to 2022. Seven studies were from Brazil, 35 - 41 6 from Iran, 42 - 47 2 from United Kingdom, 48 , 49 1 from Egypt, 50 1 from Finland, 51 and 1 from United States, 52 Regarding methodology, 15 studies were RCTs 35 - 37 ,39,41, 43 - 52 3 were non-RCT. 38 , 40 , 42 …”
Section: Resultsmentioning
confidence: 99%
“…Dear Editor, I read with great interest the article by Elhadad MA et al, "The effect of topical chamomile in the prevention of chemotherapy-induced oral mucositis: A randomized clinical trial" (Elhadad et al, 2022). I appreciate the efforts of the authors in clarifying the topical chamomile efficacy of the prevention of chemotherapy-induced oral mucositis in cancer patients.…”
Section: Letter To the Editormentioning
confidence: 99%
“…The use of phytotherapy shows satisfactory results in OM treatments, such as: chamomile [13][14][15], bilberry extract [16], Hydroalcoholic extract of Carumcarvi L [17], propolis [18] and eucalyptus hydroalcoholic extract [19]. Even though that herbal medicine is a very ancient practice, the studies related to the medical use of plants and its acceptance became more popular in the last years [20].…”
Section: Introductionmentioning
confidence: 99%